PELATIHAN BUDIDAYA LEBAH MADU SEBAGAI UPAYA PENINGKATAN KAPASITAS DAN KETAHANAN EKONOMI MASYARAKAT LERENG GUNUNG SLAMET - Rachmah, Malinda Aptika; Budiyoko; Sunendar (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Kemutug Lor Village is a village located on the slopes of Mount Slamet. The village has great potential, especially in agriculture, animal husbandry, forestry, and nature tourism. However, there is a lot of looting of trees in the protected forest of Mount Slamet for economic reasons. The purpose of this training activity is to increase the capacity of understanding, knowledge, and skills and improve the economic resilience of the Kemutug Lor Village community through professional forest honey cultivation training. The targets of this training activity are the people of Kemutug Lor Village and LMDH Wana Karya Lestari. Implementing training activities was carried out through lectures, discussions, and practices with resource persons. During the training activities, the participants were very enthusiastic and reflected in the many questions and discussions, and the participants were seen listening carefully to the explanations and practices carried out by the resource persons. The results of this training activity are an increase in the understanding, knowledge, and skills of participants in honey bee cultivation and an increase in the income of the Kemutug Lor Village community in the future.